Análisis del comportamiento de un motor asíncrono. - Cando Cando, Tony Evair (2023)
This technological proposal on the analysis of the behavior of a three-phase asynchronous motor defines a type of induction motor commonly used in various types of machinery and industrial systems. An industrial control module was designed in AutoCAD software which contains elements of force, control and electrical measurement, the combination of these elements allows different starts such as direct, star-triangle and with frequency converter subjecting the motor to a load at no load, 50% and 100% of its capacity. The behavior can be analyzed from different perspectives to understand how it works and evaluate its performance. Among the most important characteristics to consider are electrical, mechanical and thermal. Regarding the electrical characteristics, the synchronous speed, which is the speed at which the motor rotor should rotate if there were no slip, and the slip, which indicates the difference between the synchronous speed and the actual rotational speed of the rotor, stand out. Also relevant is the starting current, which is the electrical current flowing through the motor at start-up, and the efficiency, which indicates the ratio of the motor's power output to its power input. Finally, it was identified that star-delta starting reduces the starting current in three-phase motors, since, the delta configuration can be 5 times greater than the total load demand causing damage to sensitive equipment. The star configuration will reduce the voltage to 58% and the coil current to 33%, compared to the delta configuration, in addition to reducing the torque by about 33%.